THE INFLUENCE OF INFORMATION TECHNOLOGY AND TRAINING ON EMPLOYEE PERFORMANCE THROUGH COMPETENCE - YUYUN DESTI INDRAWATI; YOBERTH KORNELIUS; IRA NURIYA SANTI (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
This study aims to assess and analyze the effect of information technology on competence, the effect of training on competence, the effect of competence on employee performance, the effect of information technology on employee performance, the effect of training on employee performance through competence, and the effect of training on employee performance through competence. The research in question is quantitative. There were 47 participants in this study who were employees of the Tora Belo Regional General Hospital in Sigi Regency. The SEM-PLS approach was used to conduct hypothesis testing, and the descriptive analysis method was used to analyze the data. Competence has a substantial and favorable influence on employee performance, as shown by the analysis results. In addition, employee performance is significantly and favorably affected by information technology. However, training has a minimal and adverse effect on employee performance. In addition, employee competencies facilitate the favorable and substantial impact of information technology on employee performance. Employee performance is significantly and directly influenced by training, which is also influenced by the level of competence.